2017
DOI: 10.1002/jmrs.217
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and dosimetric predictors of late rectal bleeding of prostate cancer after TomoTherapy intensity modulated radiation therapy

Abstract: IntroductionRectal bleeding after radiotherapy impacts the quality of life of long‐term surviving prostate cancer patients. We sought to identify factors associated with late rectal bleeding following intensity modulated radiation therapy (IMRT) using TomoTherapy for prostate cancer.MethodsWe retrospectively analysed 82 patients with localised prostate cancer treated with TomoTherapy. Most patients (95.1%) received neoadjuvant and concurrent hormone therapy. Forty‐two patients (51.2%) graded as high risk using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
1
5
1
Order By: Relevance
“…In studies using HT with conventional fractionation, incidence of late grade 2 or more GI and GU toxicity ranged from 6.1-9.7% and from 1.2-10.7%, respectively (20,27,28), and bRFS rates at 3-5 years were almost ≥90% (20,28). Tomita et al reported outcomes of HT at a median dose of 78 Gy in 2 Gy fractions for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In studies using HT with conventional fractionation, incidence of late grade 2 or more GI and GU toxicity ranged from 6.1-9.7% and from 1.2-10.7%, respectively (20,27,28), and bRFS rates at 3-5 years were almost ≥90% (20,28). Tomita et al reported outcomes of HT at a median dose of 78 Gy in 2 Gy fractions for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As the most dominant OAR in cervical radiotherapy, the dose range of rectum has much clinical significance. For instance, studies show that rectum bleeding is associated with rectum high dose range [ 24]. The popular Lyman-Kutcher-Burman (LKB) NTCP model was used to fit the dose volume relationship to the clinical data [25,26].…”
Section: Normal Tissue Complication Probability (Ntcp)mentioning
confidence: 99%
“…We reported the long-term outcome concerning locally advanced prostate cancer patients treated with radiation therapy using VMAT, mainly late adverse events such as rectal bleeding. Previous studies have reported that the incidence of late rectal bleeding ranges from 5% to 24%, of which approximately 2% were grade 3 patients 5,6,[9][10][11][12][13][14][15][16][17] (Table 7). In our study, late rectal bleeding occurred in 19% of patients, of whom 5.5% and 1.4% were classified as grades 2 and 3, respectively, a finding that was similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many prostate cancers occur in elderly individuals aged ≥70 years, and many patients receive anticoagulant therapy for cardiovascular disease prior to radiation therapy. For at-risk patients such as those undergoing concomitant anticoagulant therapy 16 and with severe diabetes, careful treatment options are necessary. Currently, we have reduced the prescribed dose to 72 Gy for at-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation